Stability of membrane bound reactions - Thul, Ruediger; Falcke, Martin (American Physical Society, 2004)
We present a novel approach to the dynamics of reactions of diﬀusing chemical species with species ﬁxed in space e.g. by binding to a membrane. The non-diﬀusing reaction partners are clustered in areas with a diameter smaller than the diﬀusion length of the diﬀusing partner. The activated fraction of the ﬁxed species determines the size of an active sub-region of the cluster. Linear stability analysis reveals that diﬀusion is one of the ma jor determinants of the stability of the dynamics. We illustrate the model concept with Ca²⁺ dynamics in living cells, which has release channels as ﬁxed reaction partners. Our results suggest that spatial and temporal structures in intracellular Ca²⁺ dynamics are caused by ﬂuctuations due to the small number of channels per cluster.